The Effect Of Brain Gym On Improving Memory In Grade VI Children At Public Elementary School 86 Kendari An Experimental Study Conducted In 2024 - Wahyuni, Sri (Sahabat Publikasi Kuu, 2024)
When the learning outcomes of students are low, then often one of the reasons for the cause is the teacher who does not apply monotonous learning methods that cause a lack of interest in learning, and low motivation, some of them are also only able to understand if the teacher or lesson is favored. Activities after school are not for resting but playing gadgets or with friends. The research design used in this study is Pre-Experiment with the design used is One Group Pre and Post Test desaign. The population in this study were all 6th grade students of 86 Kendari State Elementary School as many as 68 respondents with purposive sampling technique. The results of the statistical test show that the results of the statistical test of the Mean value of the pre-test 4.00 and post-test 7.72 with SD value of pre-test 1.495 and post-test 2.081 with a significant 0.000 <0.02. The results of the analysis of the table above also obtained the value of t = 7.298> 2.567 where t count is greater than the t table value. This shows that there is an effect of brain gym on improving memory in grade VI children at public elementary school 86 Kendari. From the results of this study, it was found that there was an effect of brain gym on improving memory in grade VI children in public elementary school 86 Kendari. Suggestions for teaching staff at Kendari 86 State Elementary School to apply Brain Gym in classroom learning can be done before learning takes place or the introduction stage, during the learning process or the core activity stage, and after learning is given or the closing stage.